Answer: x=25
Explanation:
Simplifying
(2x + -10) = (65 + -1x)
Reorder the terms:
(-10 + 2x) = (65 + -1x)
Remove parenthesis around (-10 + 2x)
-10 + 2x = (65 + -1x)
Remove parenthesis around (65 + -1x)
-10 + 2x = 65 + -1x
Solving
-10 + 2x = 65 + -1x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add 'x' to each side of the equation.
-10 + 2x + x = 65 + -1x + x
Combine like terms: 2x + x = 3x
-10 + 3x = 65 + -1x + x
Combine like terms: -1x + x = 0
-10 + 3x = 65 + 0
-10 + 3x = 65
Add '10' to each side of the equation.
-10 + 10 + 3x = 65 + 10
Combine like terms: -10 + 10 = 0
0 + 3x = 65 + 10
3x = 65 + 10
Combine like terms: 65 + 10 = 75
3x = 75
Divide each side by '3'.
x = 25
Simplifying
x = 25
Sorry if its too confusing!